IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARD NO. 2 CONCERNING CASH-BASED BUDGET REALIZATION REPORTS IN HUMBANG HASUNDUTAN REGENCY - Gilberta Naibaho; Septi Lumbantobing; Iskandar Muda (JITAA : Journal Of International Taxation, Accounting And Auditing, 2025)
The Budget Realization Report (LRA) is one of the main reports in local government financial reporting that describes the realization of revenue, expenditure, and financing based on cash-based principles. Government Accounting Standards (SAP), especially PSAP Number 2, regulate the preparation of LRAs in order to provide transparent and accountable financial information. This study aims to analyze the level of suitability of the preparation of cash-based LRA as of May 31, 2025 with the provisions of PSAP Number 2. The method used is qualitative descriptive with a documentation study approach to the LRA for the 2025 period. The analysis was carried out by compa ring the content of the report with the provisions of PSAP Number 2 regarding cash-based presentation. The results of the analysis show that the preparation of in general has met the requirements of PSAP Number 2, but there is still room for improvement in terms of detail and disclosure of information so that financial reporting can be more transparent and accountable. it is recommended that local governme nts continue to improve the quality of report presentation to support responsible financial management & appropriate decision-making